2020
DOI: 10.3892/ijmm.2020.4758
|View full text |Cite
|
Sign up to set email alerts
|

Epigallocatechin‑3‑gallate inhibits self‑renewal ability of lung cancer stem‑like cells through inhibition of CLOCK

Abstract: Circadian rhythm plays an important role in diverse physiological processes. Abnormal expression of circadian rhythm genes is associated with increased risk of disease, including different types of cancer. The cancer stem cell (CSC) hypothesis suggests that there is a small subset of stem-like cells within tumors that are responsible for tumor initiation. However, the biological effect of circadian rhythm on CSCs remains largely unknown. Studies have highlighted that the circadian rhythm protein CLOCK controls… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 35 publications
(37 reference statements)
0
27
0
Order By: Relevance
“…However, in esophageal tumors, CLOCK , PER1 , PER2 , PER3 , CRY1 as well as CRY2 levels are down-regulated and their downstream proteins accordingly become disordered ( van der Watt et al, 2020 ). As for lung cancer cells, the primary circadian gene CLOCK is up-regulated in CD133+ cells, and this can also be observed in A549 and H1299 cells ( Jiang et al, 2020 ; Yoshida et al, 2013 ). A comparative analysis revealed that PER1 levels were nearly 30% those of normal tissues, PER2 was 70%, CRY1 was 66%, CRY2 was 30%, and BMAL1 was 80% in non-small cell lung cancer ( Chen et al, 2020 ).…”
Section: The Correlation Between the Circadian Clock And Tumor Biologymentioning
confidence: 91%
“…However, in esophageal tumors, CLOCK , PER1 , PER2 , PER3 , CRY1 as well as CRY2 levels are down-regulated and their downstream proteins accordingly become disordered ( van der Watt et al, 2020 ). As for lung cancer cells, the primary circadian gene CLOCK is up-regulated in CD133+ cells, and this can also be observed in A549 and H1299 cells ( Jiang et al, 2020 ; Yoshida et al, 2013 ). A comparative analysis revealed that PER1 levels were nearly 30% those of normal tissues, PER2 was 70%, CRY1 was 66%, CRY2 was 30%, and BMAL1 was 80% in non-small cell lung cancer ( Chen et al, 2020 ).…”
Section: The Correlation Between the Circadian Clock And Tumor Biologymentioning
confidence: 91%
“…Interestingly, the knockdown of CLOCK by siRNA resulted in a reduced ability for sphere formation and the inactivation of the Wnt/β-catenin signaling pathway, while treatment with EGCG repressed CLOCK expression in the spheroids. Moreover, in a xenograft model, EGCG suppressed the cancer stem-cell-like features (CD133, CD44, Sox2, Nanog and Oct4 protein) of A549 and H1299 cells by targeting CLOCK, suggesting EGCG is a compound with chronotherapeutic potential to inhibit the self-renewal capacity of lung cancer stem-like cells by modulating CLOCK [101]. In another study, it was observed that doxorubicin (DOX) altered the core clock genes and various cytokines in macrophages extracted from tumor (Lewis lung carcinoma)-bearing mice.…”
Section: Chronotherapy In Lung Cancermentioning
confidence: 95%
“…Numerous clinical trials have confirmed a strong correlation between PD-L1 expression and the OS and PFS of NSCLC patients [63,68,[81][82][83][84][85], which is deeply associated with tumour immunoresistance [86].…”
Section: Pd-l1 In Ctcsmentioning
confidence: 97%